Xanthomonas oryzae pv. oryzae, biochemical tests, rice (Oryza sativa), bacterial leaf blight (BLB) disease, Sekinchan - Jonit, N. Q.; Low, Y. C.; Tan, G. H. (Science and Education Publishing, 2016)
Bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae is one of the most devastating diseases in rice which limits the annual rice production in both tropical and temperate regions of the world. The present study was conducted to isolate, characterize and identify the Xanthomonas oryzae pv. oryzae obtained from infected rice foliar samples. Plant samples were collected from one of the major agro-ecological rice zones in Sekinchan, Peninsular Malaysia. The infected leaf samples were plated on nutrient agar and gave light yellow, circular, smooth, convex and viscous bacterial colonies. There were 15 isolates obtained and subjected to different biochemical tests. KOH test was conducted to re-confirm gram staining of all isolates. The egg yolk reaction gave negative for the eleven isolates (Xoo-1, Xoo-4, Xoo-11, Xoo-12, Xoo-13, Xoo-14, Xoo-15, Xoo-16, Xoo-17, Xoo-18 and Xoo-20) and positive for four isolates (Xoo-9, Xoo-10, Xoo-19 and XOR). Results of biochemical tests like starch hydrolysis, anaerobic nature and acid production from carbohydrates varied among the isolates. In the starch hydrolysis, nine isolates showed positive reaction. In anaerobic and acid production from carbohydrate test, nine and five isolates showed positive reaction respectively. It is about 21% isolates were similar in terms of their reactions to these tests. Based on biochemical responses it was established a genetic variability was detected in Xathamonas oryzae pv. oryzae isolates. Some of the isolates diverse from the normal pattern and had overlapping results. The phylogenetic trees showed Xoo-9 and XOR are closely related to Micrococcus aloeverae with 100% and Xanthomonas sacchari with 99% of similarity respectively. The XOR isolate showed similar characteristic to X. oryzae pv. oryzae. However, the DNA identification did not match 100% similarity to target pathogen, even though they both are from the same origin. Further study need to be carried out for comparative and functional genomics to improve our understanding of their modes of adaptation to different ecological niches and the genes that determine their pathogenicity.